Cortiços na região central de São Paulo em 2020/2021, novos olhares - Lui, Marcos Venancio Cavalcanti de Albuquerque (2022)
Tenements are a housing option for the poor in downtown São Paulo from the 1870s to the 20s of the 21st century and studies on this topic in the city have been carried out for more than a century, which we evidenced through a detailed research. bibliography on tenements where we divide it into three main categories: tenements as a complaint; the tenement as a potentiality; and the tenement as reality. 57% of the forty-nine are within the complaint category, showing the predominant bias of exposing precariousness and reporting to the public power. The work carries out a field visit in tenements in Bom Retiro, in 23 tenements in Bom Retiro, which identifies recent permanences and transformations. We detected in this study that the great subject absent from the literature are the intermediaries or owners, the tenement operators who are the articulating agent of the entire scheme. We show through seven interviews a new look at these operators, helping to fill the gap observed in the literature and show other facets coming out of the exploiter-victim binomial. that identifies recent permanences and transformations. Finally, we analyze the results of Bom Retiro with previous studies on tenements in the capital, carrying out a work of historical series of research results.